ANTIMICROBIAL ACTIVITY OF SENNA ITALICA MILL. LEAF AND PHYLLANTHUS RETICULATUS POIR FRUIT EXTRACTS - K. Deepa; P. Leela (The Bioscan, 2026)
Antimicrobial agents are substances that inhibit or eliminate pathogenic microorganisms, including bacteria and fungi, and are essential for controlling infectious diseases. The growing emergence of antimicrobial resistance has reduced the effectiveness of conventional antibiotics, creating an urgent need for alternative sources of antimicrobials. Medicinal plants represent a promising option due to their rich content of bioactive secondary metabolites. The present study evaluated the antibacterial and antifungal activity of sequential solvent extracts of S.italica Mill. and P. reticulatus Poir. Hexane, ethyl acetate, and methanolic extracts were prepared and assessed using the Kirby–Bauer disc diffusion method against selected Gram-positive and Gram-negative bacteria and fungal pathogens. The results demonstrated a solvent-dependent antimicrobial response, with methanolic extracts exhibiting significantly higher activity than non-polar extracts. The methanolic extract of S. italica showed strong antibacterial activity against Pseudomonas aeruginosa (19.40 ± 0.10 mm) and notable antifungal activity against Malassezia furfur (18.20 ± 0.20 mm). P. reticulatus extracts displayed moderate but consistent antimicrobial activity, including inhibition of Trichophyton rubrum (15.30 ± 0.10 mm). These findings highlight the importance of solvent polarity in extracting antimicrobial compounds and support the potential of S. italica and P.reticulatus as natural sources of antibacterial and antifungal agents. This study provides a robust foundation for future research and highlights plant-based solutions in combating antibiotic resistance. Keywords Antifungal, Antifungal, Bioactive, Pathogen, Senna italica; Phyllanthus reticulatus.